IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 47 TAHUN 2008 TENTANG PROGRAM WAJIB BELAJAR 9 TAHUN DALAM PEMENUHAN HAK DASAR ANAK - Maulida Agustina (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACTThe opening of the 1945 constitution dedared the 4 paragraph states that 1 of the tasks is educating the nation and for it anyway then every citizen has the right to a decent education services in accordance with the times and the advancement of science.as for the formulation of the problem in the study of how the implementation of compulsory education system in samarinda city of 9 year based on Peraturan Pemerintah Number 47 of 2008 and how the roles and responsibilities of Pemerintah Daerah on the implementation of the Samarinda city of 9 year compulsory education program.purpose of this study was to determine the extent to which the education system is compulsory of 9 year in the Samarinda city and the extent to whicb the roles and responsibilities of Pemerintah Daerah in the implementation of 9 year compulsory education program.this research method is to use a normative juridical method is by using the resources of the library sources and method namely the juridical sociological research in the field.the result of research by the author to convey here that how the implementation of 9 year compulsory education program in the damarinda city and how the roles and responsibilities of Pemerintah Daerah on the implementation of the samarinda city of 9 year compulsory education program.as for suggestions that need to be considered in the implementation of 9 year compulsory education program in tehe samarinda city that program implementation is achieved with a amaximum.Keyword : implementation and children’s rights